Biogeography rather than association with cyanobacteria structures symbiotic microbial communities in the marine sponge Petrosia ficiformis - Burgsdorf, Ilia; Erwin, Patrick M.; López-Legentil, Susanna; Cerrano, Carlo; Haber, Markus; Frenk, Sammy; Steindler, Laura (Frontiers in Microbiology, 2014)
The sponge Petrosia ficiformis is ubiquitous in the Mediterranean Sea and Eastern Atlantic Ocean hosting a diverse assembly of bacteria, including, in illuminated sites, cyanobacteria. Two closely related sponge color morphs have been described, one inside caves and at their entrance (white/pink), and one on the rocky cliffs (violet). The presence of the different morphs and their ubiquity in the Mediterranean (from North-West to South-East) provides an opportunity to examine which factors mostly affect the associated microbial communities in this species: (i) presence of phototrophic symbionts or (ii) biogeography. 16S rRNA gene tag pyrosequencing data of the microbial communities revealed that Chloroflexi, Gammaproteobacteria and Acidobacteria dominated the bacterial communities of all sponges analyzed. Chlorophyll a content, TEM observations and DNA sequence data confirmed the presence of the cyanobacterium Synechococcus feldmannii in violet and pink morphs of P. ficiformis and their absence in white color morphs. Rather than cyanobacterial symbionts (i.e. color morphs) accounting for variability in microbial symbiont communities, a biogeographic trend was observed between P. ficiformis collected in Israel and Italy. Analyses of partial 18S rRNA and mitochondrial cytochrome c oxidase subunit I (COX1) gene sequences revealed consistent genetic divergence between the violet and pink-white morphotypes of P. ficiformis. Overall, data indicated that microbial symbiont communities were more similar in genetically distinct P. ficiformis from the same location, than genetically similar P. ficiformis from distant locations.